Photodynamic therapy with light-emitting diode arrays producing different light fields induces apoptosis and necrosis in gastrointestinal cancer - Shi, Xiafei; Yin, Huijuan; Dong, Xiaoxi; Li, Hongxiao; Li, Yingxin (Frontiers in Oncology, 2022)
Light-emitting diodes (LEDs) have become a new light source for photodynamic therapy (PDT) because of their excellent optical properties, small size, and low cost. LED arrays have so far been designed to meet the need for accurate illumination of irregular lesions. However, LED arrays determine not only the shape of the illuminated spot but also the light field, which has a significant impact on the efficacy of PDT. We designed three types of LED arrays producing different light fields, namely an intensive LED array for a uniform light field, a sparse LED array for a non-uniform light field, and a point LED array for a Gaussian-like light field, and investigated the effect and mechanism of these light fields on PDT for gastrointestinal cancer both in vitro and in vivo. We found that intensive LED-PDT induced earlier and more serious cell death, including apoptosis and necrosis, than sparse LED-PDT and point LED-PDT. Among the three LED arrays, the intensive LED array induced cells to produce more differential proteins (DEPs), mainly related to mitochondria, ribosomes, and nucleic acids. DEPs in cells subjected to sparse LED- and point LED-PDT were mainly involved in extracellular activities. For MGC-803 tumor-bearing mice, intensive LED-PDT and point LED-PDT had better tumor ablation effect than sparse LED-PDT. Notably, recurrence was observed on day 7 after sparse LED-PDT. VCAM-1 and ICAM-1 were highly expressed in sparse LEDs-PDT treated tumor tissues and were associated tumor angiogenesis, which in turn lead to poor tumor suppression.Therefore, the type of LED array significantly affected the performance of PDT for gastrointestinal cancer. Uniform light field with low power densities work better than non-uniform and Gaussian-like light fields.